MRS. DALLOWAY : A GYNOCRITICAL STUDY - K. Singh, Dr Bimlesh (Innovative Research Thoughts, 2017)
Virginia Woolf is a modern novelist, par excellence. She expresses profound and mature vision of Life in her novels and other writings. Her novels - Mrs. Dalloway, To the Lighthouse, Jacob’s Room. The Waves, The Voyage Out are in-depth expression of the complexity of life. The complexity of her vision owes to her probing and exploration of the psyche, the inner world of characters. In fact, Virginia Woolf is, primarily, concerned with the realism of spirit and unbroken flow of consciousness which is timeless and immortal.